2015
DOI: 10.1002/14651858.cd000230.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation for improving pregnancy and infant outcome

Abstract: Analysis 1.12. Comparison 1 Zinc supplementation versus no zinc (with or without placebo), Outcome 12 Meconium in liquor..... Analysis 1.13. Comparison 1 Zinc supplementation versus no zinc (with or without placebo), Outcome 13 Caesarean section...... Analysis 1.14. Comparison 1 Zinc supplementation versus no zinc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
2
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 220 publications
(169 citation statements)
references
References 82 publications
9
146
2
12
Order By: Relevance
“…Research carried out among pregnant women in developed and developing countries has shown a positive correlation between zinc supplementation during pregnancy and the birth weight of the child. A significant association was shown between zinc supplementation during pregnancy and a decrease in the incidence of premature births [16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Research carried out among pregnant women in developed and developing countries has shown a positive correlation between zinc supplementation during pregnancy and the birth weight of the child. A significant association was shown between zinc supplementation during pregnancy and a decrease in the incidence of premature births [16].…”
Section: Discussionmentioning
confidence: 97%
“…Zinc is essential to the proper functioning of certain hormones, for instance insulin. However, an excessive intake of zinc can have the adverse effect of suppressing copper absorption [14][15][16]. The daily requirement for zinc during pregnancy ranges from 11-12 mg. Good sources of dietary zinc include whole wheat bread, buckwheat, dry legumes, cheeses and seafood, and meat from where it is best absorbed.…”
Section: Zincmentioning
confidence: 99%
“…30 The number of included participants in the reviews ranged from 603 participants 41 to over 310 000 participants. 24 Supplementation with vitamins was reported in five reviews, 24-26 45 46 supplementation with minerals in eight reviews [27][28][29][30][31][32][33][34] and MMN supplementation was assessed in three reviews. [35][36][37] There was one review on protein supplementation and nutritional education 38 and two reviews reported on marine oil and fatty acid supplementation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…21,23 Fourth, zinc is important for neuron formation, migration, and synapse generation, 24 and, if given as a supplement, can reduce the risk of preterm birth. 25 Fifth, tryptophan is an essential amino acid needed for the formation of neurotransmitters. 26 Sixth, Ω-3 fatty acids are necessary for the development of neural cell membranes.…”
Section: The Impact Of Preconception and Prenatal Maternal Nutrition mentioning
confidence: 99%